2020
DOI: 10.21203/rs.3.rs-44825/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exposure to ZnO/TiO2 Nanoparticles Affects Health Outcomes in Cosmetics Salesclerks

Abstract: Background: Concerns about the effects of nanoparticles (NPs) on human health are being raised by researchers because the risks of nanocosmetics like sunscreen are unknown. Methods: We explored the association between urinary oxidative stress markers and exposure of cosmetics salesclerks to 20 cosmetics which might contain titanium dioxide (TiO2)/zinc oxide (ZnO) NPs. We then recruited 40 cosmetics salesclerks and 24 clothing salesclerks and categorized them based on their exposure to ZnO and TiO2 NPs. Results… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 22 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Several recent studies have reported that oil-derived PAHs could stimulate reactive oxygen species (ROS) production during their biotransformation, resulting in an elevation of ROS levels in marine organisms [ 2 , 29 , 30 ]. Overelevation of ROS levels could further induce oxidative damage of the biomacromolecules (including DNA, proteins, and lipids) [ 31 , 32 ], which is known as the primary mechanism involved in cell damage, apoptosis, and tissue injury in marine organisms exposed to oil-derived PAHs [ 29 , 33 , 34 , 35 , 36 ]. Additionally, numerous studies have documented that elevated temperature could cause physiological (e.g., increased oxygen consumption) and histological (e.g., tissue injury) changes in marine organisms, and it has been suggested that elevated temperature could also disturb the balance between endogenous and exogenous ROS levels and thereby cause an incapacity of the antioxidant defense system [ 23 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have reported that oil-derived PAHs could stimulate reactive oxygen species (ROS) production during their biotransformation, resulting in an elevation of ROS levels in marine organisms [ 2 , 29 , 30 ]. Overelevation of ROS levels could further induce oxidative damage of the biomacromolecules (including DNA, proteins, and lipids) [ 31 , 32 ], which is known as the primary mechanism involved in cell damage, apoptosis, and tissue injury in marine organisms exposed to oil-derived PAHs [ 29 , 33 , 34 , 35 , 36 ]. Additionally, numerous studies have documented that elevated temperature could cause physiological (e.g., increased oxygen consumption) and histological (e.g., tissue injury) changes in marine organisms, and it has been suggested that elevated temperature could also disturb the balance between endogenous and exogenous ROS levels and thereby cause an incapacity of the antioxidant defense system [ 23 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%